A struggle for translation: An actor-network analysis of Chilean school violence and school climate policies - López, Verónica; Sisto, Vicente; Baleriola, Enrique; García, Antonio; Carrasco-Aguilar, Claudia; Núñez, Carmen Gloria; Valdés, René (Sage, 2019)
In the last six years, Chile has carried out major reforms in school climate policy. However, these reforms are tied to two different realities that conflict with each other: a formative reality, which promotes a school climate of local decision-making and the improvement of school performance; and a punitive reality, which prioritizes improvement in the school climate through accountability protocols and regulations. We used Actor-Network Theory to describe the network of actors that underlie these realities. We analyzed key documents and conducted active interviews with actors responsible for the design and implementation of these policies. Results show that the assembled network enacts an accountability reality by means of the Law on Assurance of the Quality of Education, with key devices and s-objects performing the network. However, this enacted reality is at odds with a logic of school improvement that is still defended by the Ministry of Education, an actor that is no longer the main source of translation in the network. These results are discussed in light of the so-called “global triumph” of New Public Management through the dissemination of specific instruments that bring together subjects and objects in enacting the reality of accountability.
https://openpolicyfinder.jisc.ac.uk/id/publication/9123
Keywords: Violencia en la escuela; Administración y organización escolar; Actor network theory; School climate policy; Quality assurance; School violence